Carbon Fiber Aerogel Made from Raw Cotton: A Novel, Efficient and Recyclable Sorbent for Oils and Organic Solvents. (19th August 2013) - Bi, Hengchang; Yin, Zongyou; Cao, Xiehong; Xie, Xiao; Tan, Chaoliang; Huang, Xiao; Chen, Bo; Chen, Fangtao; Yang, Qingling; Bu, Xinyang; Lu, Xuehong; Sun, Litao; et al.
<x xml:space="preserve">Abstract</x> Twisted carbon fiber (TCF) aerogel with good selective sorption is produced in large scale by using raw cotton as the precursor. TCF aerogel shows highly efficient sorption of organic liquids (pump oil: up to 192 times its own weight; chloroform: up to 115 times its own weight). Moreover, it could be regenerated many times without decrease of sorption capacity by distillation, combustion or squeezing, which depends on the type of pollutants. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>